The Effect of Out-of-School Learning Environments on Grade 6 Students' Interest Levels for STEM Professions - Saadet Deniz Korkmaz; Selda Topal (Mimbar Sekolah Dasar, 2023)
Students should be provided with more meaningful learning experiences to attract more students to STEM careers, Out-of-School learning environments can offer students exciting and motivating learning opportunities that formal environments cannot provide. Therefore, national education reforms in many countries that are working on popularizing STEM career have shifted STEM education to out-of-School learning environments. In this study which used a quasi-experimental design with pretest-posttest control group, the effect of out-of-School learning environments on middle school 6th grade students' interest in STEM field has been investigated. The participants of the research consisted of 14 girls and 22 boys in total 36 students. Within the scope of the research, a STEM education program consisting of 6 different learning environments, four of which is out of school and two in school, has been prepared. The training program of the study was completed in 16 weeks. In the research, the pretest-posttest control group research model was used, and the data were collected using the STEM career interest scale. The results obtained from this study show that non-formal education in out-of-School learning environments is effective in the orientation of secondary school students to STEM career fields especially Science related professions.